Foreword - J.-A. van den Berg; J. Meyer (Acta Theologica)
The eye is the window or light to the soul. A window lets light in. In many churches worldwide, the sunlight is bright and colourful as it brings to life awe-inspiring images through stained-glass windows. The front page of the Festchrift for colleague Kobus Schoeman depicts one of the stained-glass windows of the DRC mother church in Stellenbosch. As this work of art is rich in symbolism and begs to be unlocked for a deeper meaning, so are these contributions in the Festchrift, dedicated to colleague Kobus Schoeman on the occasion of his retirement. As the windows in a church convey the gospel, so do the different contributions.